Assembling a Bluetooth Speaker Prototype as a Lecture Teaching Material - Meldra, Delia (Jurnal Liga Ilmu Serantau, 2024)
The development of student creativity depends on the lecture method determined. The more often students create work, the more their ability to create something increases. This is also stated in the curriculum issued by the government, namely the project-based prototype curriculum. Based on this, research on assembling Bluetooth speaker prototypes was created as lecture teaching material so that students are able to develop speaker prototypes that are more varied in terms of basic materials (can be from gonggong seafood waste and so on), shapes, development ideas, thinking about market targets, and so on. . A speaker or also known as a loudspeaker is a device that converts electrical signals into audio frequencies (sound) by vibrating membrane-shaped components to vibrate the air so that sound waves are heard that reach the eardrum and can be heard as sound. This speaker uses Bluetooth as a medium to connect sound processing devices to the speaker. This Bluetooth speaker still uses AC power, which also aims to increase development ideas if it uses DC in the future. The resulting speaker can work well using Bluetooth with several shortcomings regarding sound dampening which in the future could be a process for improvement.